'Entering a gigantic maze:' The ambivalent presence of previous-life memories in Druze discourse. (June 2019) - Nigst, Lorenz
According to the Druze notion of transmigration ( taqammuṣ ), whenever someone dies, his or her soul moves into the body of a newborn Druze of the same sex. While this makes the Druze feel that they belong together in a more fundamental way because they are 'born in each other's houses' (Oppenheimer), it is more ambivalent the moment children start to 'speak' about previous lives in another family. Allowing the 'return' of someone lost to death and potentially bringing two such houses in closer relation, 'speaking' also requires coming to terms with conflicting belonging.